2015
DOI: 10.1186/s12866-015-0433-5
|View full text |Cite
|
Sign up to set email alerts
|

Extensive characterization of Campylobacter jejuni chicken isolates to uncover genes involved in the ability to compete for gut colonization

Abstract: Background: Campylobacter jejuni is responsible for human foodborne enteritis. This bacterium is a remarkable colonizer of the chicken gut, with some strains outcompeting others for colonization. To better understand this phenomenon, the objective of this study was to extensively characterize the phenotypic performance of C. jejuni chicken strains and associate their gut colonizing ability with specific genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…jejuni containing an equal amount of our lab strains A2008a and G2008b. These 2 strains, recovered from fresh chicken caecal content, were previously extensively characterized for their ability to colonized the chicken and compete for colonization, even in the presence of essential oils given as a feed additive [ 26 , 27 ]. Each chicken received 10 4 CFU of each strain.…”
Section: Methodsmentioning
confidence: 99%
“…jejuni containing an equal amount of our lab strains A2008a and G2008b. These 2 strains, recovered from fresh chicken caecal content, were previously extensively characterized for their ability to colonized the chicken and compete for colonization, even in the presence of essential oils given as a feed additive [ 26 , 27 ]. Each chicken received 10 4 CFU of each strain.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we observed that many of the C. jejuni subtypes recovered from cattle were also responsible for infections in people living in the study region. Although chickens are thought to be the primary reservoir of CRS [59], there are locations where this does not appear to be true. For example, in Finland, cattle appear to be an important primary reservoir of CRS [60].…”
Section: Discussionmentioning
confidence: 99%
“…The avian reservoir is the predominant source of C. jejuni infections, which have been strongly linked to contaminated retail chicken by numerous studies [8,9]. As a commensal organism with high prevalence (10 9 CFU/g) in chicken ceca, C. jejuni easily contaminates carcasses of slaughtered birds [10]. Davis and colleagues demonstrated experimentally that Campylobacter survives well on both chicken skin and meat at refrigerated temperatures [11].…”
Section: Significance Of Campylobacter Jejuni As a Pathogenmentioning
confidence: 99%